Yield and yield components of sweet corn (Zea Mays L) grown under different tillage methods. - Ahmad, Desa; Wayayok, Aimrun; Shamsabadi, Hossein (2011)

(untitled)
Field experiments were conducted to investigate the effects of three tillage systems on sweetcorn yield and selected yield components.